Peculiarities of the competitive activity of taekwondo players aged 12-13 years before and after the changes in the rules - Sergiy Strelchuk; Olena Lukina; Viktor Savchenko; Wojciech J. Cynarski; Mario Baić; Ioannis Barbas; Georgiy Korobeynikov (H.S. Skovoroda Kharkiv National Pedagogical University, 2022)
Purpose: improving the technical and tactical readiness of qualified taekwondo wrestlers at the stage of specialized basic training to improve the effectiveness of competitive activity. Material and methods. The study involved 30 athletes aged 12-13 years. Athletes are engaged in WTF taekwondo in the Dnepropetrovsk region. The research was carried out on the basis of the Communal out-of-school educational institution "City Specialized Children's and Youth Sports School of the Olympic Reserve" of the Dnipro City Council (Taekwondo Department of the WTF) and the sports club "Bars" (Dnipro). Created control and experimental groups in the amount of 15 young men in each group. Anthropometric methods, the index method were used; pedagogical methods for studying the physical and technical-tactical readiness of taekwondo fighters aged 12-13, analysis of video recordings of competitive fights of qualified taekwondo fighters in weight categories up to 33 kg, up to 37 kg, up to 41 kg, up to 45 kg, up to 49 kg, up to 53 kg, up to 57 kg ; methods of mathematical statistics. Results. After conducting a pedagogical experiment based on the results of general physical training among athletes in the experimental group, the increase in performance indicators was from 8.97% to 54.91%; in athletes of the control group - from 1.90% to 31.03%. Also, the taekwondo players of the experimental group significantly outweighed the athletes from the control group for all indicators of special physical fitness, the increase in indicators was from 10.79% to 32.30%; in the control group - from 1.25% to 17.62%. The analysis of performance indicators showed that the athletes of the experimental group significantly reduced all indicators (p < 0.01), in addition to the number of effective performance programs. Indicators of technical and tactical readiness among athletes in the control group grew from 2.38% to 19.85%; in taekwondo players of the experimental group, the increase in indicators of claves was from 13.22% to 56.53%. Conclusion. Analysis of the scientific and methodological literature on the problem of training taekwondoists at the stage of specialized basic training revealed a number of problematic issues. This concerns the features of improving the process of technical and tactical training of taekwondo cadets. The structure of the annual training of taekwondoists at the stage of specialized basic training has been developed and experimentally substantiated, which is built taking into account the individual style of conducting a competitive taekwondo duel, the manifestation of physical qualities and the calendar of competitions. An improvement in the level of physical fitness of taekwondo wrestlers, a better performance of complex technical and tactical actions and a higher efficiency of indicators of the competitive activity of athletes have been established. It has been determined that the most dominant and effective fighting styles are game and tempo, which is associated with the specifics of the WTF taekwondo and the rules of the competition.